KLAUZULA GENERALNA „DOBRYCH OBYCZAJÓW” - UJĘCIE TEORETYCZNE - Żurawik, Artur (Wydział Prawa i Administracji UAM, 2009)
The general clause of “good morals” is currently one of the most popular general clauses referred to by the Polish legislator. However, due to scarce literature on that subject, the knowledge of it is superficial and there is no agreement as to how it should be understood. The same problem was observed in the judicial decisions which lacked a uniform approach. The paper systemises the conceptions that have been formed so far, analysing their shortcomings and flows. On that basis, the author presents his own understanding of the clause of “good morals”.
GENERAL CLAUSE OF “GOOD MORALS”: A THEORETICAL APPROACH